Development of Web-Based Isim Dhamir Interactive Learning Media for Class XI Madrasah Aliyah Students - M Bakiruddin; Asep Maulana; Abdur Rosid (Abjadia : International Journal of Education, 2026)
This study aims to develop a web-based interactive learning media on isim dhamir to improve the comprehension and learning autonomy of eleventh-grade students at MA Miftahul Ulum Al-Azizah. The study stems from students’ low interest in learning Arabic grammar, mainly due to the use of conventional teaching methods that do not align with the characteristics of digital-native learners. The research employed the Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Validation results showed a content feasibility level of 97.72% and a design quality score of 96.21%, indicating that the media is highly appropriate and engaging. A limited trial was conducted with 21 students as the sample. In the effectiveness test, a Paired Sample T-Test yielded a Sig. (2-tailed) value of 0.000 < 0.05, indicating a statistically significant difference between pre-test and post-test results. The students’ average score increased from 24.6 to 85.4, with a gain of 60.8 points. Moreover, the correlation value of r = 0.666 demonstrated a strong positive relationship between the two scores. The developed product includes explanations of isim dhamir, interactive quizzes, educational games, and an online score-tracking system. The findings confirm that this media effectively enhances learning outcomes and makes the learning process more engaging. However, the study is limited by its small sample size and focus on a single grammatical topic.